Creativity and legacy: body adornments at the archaeological site of Nejapa, Nicaragua (Raíces: Revista de Ciencias Sociales y Políticas, 2018)
contexts domestic archaeological Nejapa, in the Department of Managua by using this metric analysis techniques and morphological aiming to achieve a detailed characterization of the variability of designs in the archaeological record. The results hold the body adornments to symbolize a non-verbal language that convey information essential to our social and cultural nature are eventually linked to tradition and the identity of the local population settled in this area of the Nicaraguan capital.
Keywords: Body adornments; interpretative approach; material culture; identity; Nejapa Nicaragua